2006
DOI: 10.1080/00015458.2006.11679875
|View full text |Cite
|
Sign up to set email alerts
|

A Ruptured Gastrointestinal Stromal Tumour of the Transverse Mesocolon: a Case Report

Abstract: We discuss the long history of a patient still alive with a primary gastrointestinal stromal tumour (GIST) of the transverse mesocolon: initially it presented as an acute complication, namely a haemorrhagic shock caused by rupture of the tumour and it recurred twice locally in the years following primary resection. Each time, a macroscopically complete resection could be achieved. Six years after the resection of the primary tumour, a liver metastasis was discovered, which was removed by radio frequency ablati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 5 publications
(8 reference statements)
1
19
1
Order By: Relevance
“…eGISTs of the mesocolon have been reported in the literature only twice by Jakobs et al [12] and Paparelli et al [13]. However, they did not perform a genetic analysis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…eGISTs of the mesocolon have been reported in the literature only twice by Jakobs et al [12] and Paparelli et al [13]. However, they did not perform a genetic analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Miettinen et al [11] reported 13 cases of eGISTs in the omentum and 10 cases of eGISTs in the mesentery. However, eGIST of the mesocolon has been rarely reported [12,13]. The author herein reports a case of eGIST of the transverse mesocolon with a point mutation of the PDG-FRA gene but without mutations of the c-kit gene.…”
Section: Introductionmentioning
confidence: 95%
“…Seven GISTs arose from the stomach 10,11,13,15,19,21 and four from the small intestine. [12][13][14]20 One case each originated from the mesocolon, 16 esophagus, 17 and greater omentum. 18 Depending on the location of the GIST, it may rupture into the abdominal cavity, resulting in ascites, hemoperitoneum, peritonitis, or features mimicking appendicitis if it originates in the small bowel.…”
Section: Discussionmentioning
confidence: 99%
“…Our review of the literature and a Medline search on spontaneously ruptured GISTs identifi ed only 15 cases. [10][11][12][13][14][15][16][17][18][19][20][21] In all cases, the tumor size was >5 cm, 12 of the 15 patients were older than 60 years, and the male-tofemale ratio was 2 : 1. Seven GISTs arose from the stomach 10,11,13,15,19,21 and four from the small intestine.…”
Section: Discussionmentioning
confidence: 99%
“…7 To our knowledge, a ruptured GIST with pneumoperitoneum has not been previously reported. We describe surgical correction, and histopathologic findings of a ruptured primary GIST 8 . In our patient, the operation was successful, and he did well after surgery.…”
Section: Discussionmentioning
confidence: 99%